Mild, calcium catalysed Beckmann rearrangements - Kiely-Collins, H. J.; Sechi, I.; Brennan, P. E.; McLaughlin, M. G. (Chemical communications (Cambridge, England), 2018)
A mild calcium catalysed Beckmann rearrangement has been realised, which forgoes the more traditional harsh reactions conditions associated with the transformation. The catalyst system is shown to be tolerant towards a wide variety of functional groups relevant to natural product synthesis and medicinal chemistry and the synthetic utility of the reaction has also been investigated. A preliminary mechanistic investigation was performed to understand the nature of the incoming nucleophile and a possible reaction pathway is described.